The Role Of Good Corporate Governance On Fırm Value: Analysıs Of Influencıng Factors - Siti Nisaa Ullatifah; Intan Nurul Aini; Mohamad Fajri; Agung Yulianto (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The objective of this study is to examine the impact of Corporate Social Responsibility (CSR), profitability, capital structure, and Good Corporate Governance on the value of mining businesses listed on the Indonesia Stock Exchange. The research employs a quantitative methodology with a comparative causal approach to examine the correlation between the dependent variable (firm value) and the independent variables (CSR, profitability, capital structure, and Good Corporate Governance). This study utilises secondary data extracted from the financial statements of mining industry companies that are publicly traded on the Indonesia Stock Exchange throughout the period of 2020-2022. The findings indicate that the capital structure, specifically the Debt to Equity Ratio (DER), has a positive and statistically significant impact on firm value. This means that as the DER value of a company increases, the company's performance improves. However, it has been found that CSR disclosure, profitability, and Good Corporate Governance do not have a substantial impact on the value of the company.